The potential of AMMI analysis for field assessment of Musa genotypes to virus infection - Ortíz, R. (1996)
Virus-like symptoms (due to banana streak virus, cucumber mosaic virus, or both) have been observed in plants of Musa hybrids (TMPx) and local landraces included in multilocational trials in sub-Saharan Africa. Virus-like symptom incidence in these multilocational trials was analyzed using the additive main effect multiplicative interaction (AMMI) model. There were significant differences in virus-like symptom incidence among environments, which was highest in the cool, rainy season (14% to 42%) and lowest in the warm, dry season (<10%). Genotypes showed significantly different responses to virus(es), which depended on the environment. There were no plants of AA and AAA bananas showing virus-like symptoms (0% incidence), whereas ABB cooking bananas and a cooking banana hybrid (ABB x AA) seldom showed virus-like symptoms (<2% incidence). The AAB French plantains appeared to have a similar genotypic response to virus(es) (about 10% virus-like symptom incidence) and were regarded as less susceptible than the False Horn plantain ‘Agbagba', which showed virus-like symptoms in most of the environments (average 21% incidence). Hence, ‘Agbagba' should be considered a susceptible indicator host because it has a stable susceptible host response to Musa virus(es).Plantain hybrids (AAB x AA) showed virus-like symptoms; however, there were significant differences in genotypic response to the virus(es) among various hybrids (11% to60%). Epistasis due to transgressive segregation may control the susceptibility of TMP x germplasm to Musa virus(es). The AMMI1 model revealed that an increase in clonal susceptibility resulted in a more unstable response to the virus. Similarly, phenotypicin stability was associated with an increase in clonal resistance. Environments with very low (dry season) or very high (rainy season) incidence of virus-like symptoms had unstable virus expression. Scoring virus symptoms in cool environments with low rainfall and low potential evapotranspiration provided an unbiased assessment of genotypic response to Musa virus(es). The AMMI2 model showed that seasonal rather than locational diversity accounted for most of the interaction patterns. This finding may indicate a low level of strain differentiation in the region.